Natural grasslands converted to afforested lands and abandoned lands decreasing soil carbon stability and storage, respectively, in the China’s Loess Plateau - Yao Zhong; Yumei Li; Xuemao Zhao (PLoS ONE, 2025)
Active particulate organic carbon (POC) and inert mineral-associated organic carbon (MAOC) play critical roles in regulating and predicting global climate change. However, our understanding remains limited regarding how land-use changes differentially affect these two carbon fractions and their underlying driving mechanisms. In this study, we applied a physical fractionation approach to examine changes in the carbon content and mass fractions of particulate organic matter (POM) and mineral-associated organic matter (MAOM) following the conversion of grasslands to forested or abandoned lands on the Chinese Loess Plateau. This work provides the first systematic quantification of the trade-offs among different land-use types with respect to distinct soil carbon fractions in this region. The results revealed that land use significantly altered the distribution of carbon fractions. Although afforestation increased POC contents in both soil layers (9.70 and 7.82 g·kg ⁻ ¹, respectively), it markedly reduced the more stable MAOC contents (from 9.53 and 9.62 g·kg ⁻ ¹ to 7.53 and 6.08 g·kg ⁻ ¹ in the 0–0.15 m and 0.15–0.30 m layers, respectively) and MAOM mass fractions (from 77.46% to 68.16% and from 78.69% to 71.61%). In contrast, land abandonment led to an overall decline in both carbon fractions. Mechanistically, this study revealed distinct dominant drivers for POC and MAOC: soil physicochemical properties primarily governed POC variation (68.15%), whereas microbial communities controlled MAOC variation (67.01%). Notably, bacterial β-diversity exhibited a significant negative correlation with MAOC content, offering a new perspective on the role of microbes in carbon stabilization. In summary, grassland afforestation reduced soil carbon stability by inhibiting MAOC formation, while land abandonment decreased the total soil carbon pool. These findings suggest that maintaining natural grasslands may be the most effective approach for soil carbon conservation on the Loess Plateau, and that afforestation strategies should be carefully evaluated for their potential impacts on carbon stability.